Tinjauan Roma 15: 5-6 untuk Meningkatkan Kerukunan Intern Orang Percaya Masa Kini - Asih Rachmani Endang Sumiwi; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Berita Hidup, 2021)
Harmony in Christianity is the teaching of Jesus that must be applied in loving others because the love taught by the Lord Jesus is a love that brings peace that can bring good to all people. Perspective review of Romans 15: 5-6 to increase the internal harmony of believers today. By using the Literature literature method, harmony that is built in the community and intern of religious communities can be seen and reviewed from the Bible in Romans 15: 5-6. Because as a basis and understanding and knowledge of harmony, believers unite the voice, heart and all religious components to be a blessing. The theme of perspective is Romans 15: 5-6 to enhance the internal harmony of believers today. It is a study that can be applied to believers how important it is to be light in harmony in the internal religion, so it is hoped that believers must understand and apply the Theological Review of Rome 15: 5-6, then believers have a role, that is, believers must bring harmony and finally believers making harmony among congregations a priority taught in Christian Education.Kerukunan dalam kristenan adalah ajaran Yesus yang wajib diterapkan dalam mengasihi sesama karena kasih yang diajarkan Tuhan Yesus adalah kasih yang membawa damai yang dapat membawa kebaikan bagi semua orang. Tinjauan Roma 15:5-6 untuk meningkatkan kerukunan intern orang percaya masa kini. Dengan menggunakan metode literature pustaka Kerukunan yang dibangun dalam komunitas maupun intern umat beragama dapat dilihat dan ditinjau dari Alkitab dalam Kitab Roma 15:5-6. Karena sebagai dasar dan pemahaman dan pengetahuan tentang kerukunan maka orang percaya menyatukan suara, hati dan seluruh komponen keagamaan untuk dapat menjadi berkat. Tema Tinjauan Roma 15: 5-6 untuk meningkatkan kerukunan intern orang percaya masa kini. Adalah kajian yang dapat diterapkan bagi orang percaya bagaimana pentingnya menjadi terang dalm kerukunan di intern agama mak diharapkan orang percaya harus memahami dan mengaplikatifkan Tinjaun Teologi Roma 15:5-6, lalu orang percaya memiliki Peran yaitu orang percaya harus membawa kerukunan dan yang terakhir orang percaya menjadikan kerukunan antar jemaat menjadi prioritas yang diajarkan dalam Pendidikan Kristen.